Pengaruh Tingkat Inflasi Dan Suku Bunga Bank Bank Indonesia Terhadap Kurs Rupiah/Dolar Amerika Serikat - Faaz Enver; Haider Abdad; Khaleed Jalal; Chan Darakhsha (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
The exchange rate is the value of one unit of local currency for one unit of foreign currency. Currency exchange rates are one of the most important economic elements that affect a country. Currency changes may have a sizeable effect on various sectors of the economy, including international trade, foreign investment, inflation, and general economic stability. The analytical method used in this study is to see the effect of the inflation rate (X1) and Bank Indonesia interest rates (X2) as independent variables on the US rupiah/dollar exchange rate for the 2018 – 2022 period (Y) as the dependent variable, namely Statistical Descriptive Analysis and Regression Analysis Multiple Linear. The results of the study show that the inflation rate has a positive effect on the rupiah/US dollar exchange rate and Bank Indonesia interest rates have a negative effect on the rupiah/US dollar exchange rate.